The Analysis of OmpA and Rz/Rz1 of Lytic Bacteriophage from Surabaya, Indonesia - Tessa Sjahriani; Eddy Bagus Wasito; Wiwiek Tyasningsih (Scientifica)
A good strategy to conquer the Escherichia coli-cause food-borne disease could be bacteriophages. Porins are a type of β-barrel proteins with diffuse channels and OmpA, which has a role in hydrophilic transport, is the most frequent porin in E. coli; it was also chosen as the potential receptor of the phage. And the Rz/Rz1 was engaged in the breakup of the host bacterial external membrane. This study aimed to analyze the amino acid of OmpA and Rz/Rz1 of lytic bacteriophage from Surabaya, Indonesia. This study employed a sample of 8 bacteriophages from the previous study. The OmpA analysis method was mass spectrometry. Rz/Rz1 was analyzed using PCR, DNA sequencing, Expasy Translation, and Expasy ProtParam. The result obtained 10% to 29% sequence coverage of OmpA, carrying the ligand-binding site. The Rz/Rz1 gene shares a high percentage of 97.04% to 98.89% identities with the Siphoviridae isolate ctTwQ4, partial genome, and Myoviridae isolate cthRA4, partial genome. The Mann–Whitney statistical tests indicate the significant differences between Alanine, Aspartate, Glycine, Proline, Serine (p=0.011), Asparagine, Cysteine (p=0.009), Isoleucine (p=0.043), Lysine (p=0.034), Methionine (p=0.001), Threonine (p=0.018), and Tryptophan (p=0.007) of OmpA and Rz/Rz1. The conclusion obtained from this study is the fact that OmpA acts as Phage 1, Phage 2, Phage 3, Phage 5, and Phage 6 receptors for its peptide composition comprising the ligand binding site, and Rz/Rz1 participates in host bacteria lysis.